Islamic Study Schedule Search Website in Jakarta with Automatic WhatsApp Reminder Feature Using Extreme Programming Method - Wicaksono, Fahmi Perdana; Galuh Saputri (Jurnal Inotera, 2026)
This paper presents the development of a website for searching Islamic study schedules in Jakarta equipped with an automatic reminder feature via WhatsApp. The system is designed for Muslim residents in Jakarta to provide easy access to accurate and up-to-date information on Islamic study activities. Users can search schedules based on location, study theme, and preacher. The reminder feature is integrated with WhatsApp to automatically notify users before scheduled activities. The development follows the Extreme Programming (XP) methodology, which includes planning, design, coding, and testing. System testing demonstrates that all implemented features function according to requirements.